Effect of electroacupuncture on the intestinal microflora in rats with stress urinary incontinence - Li, Chaonan; Qu, Zhiyu; Liu, Jiandang; Ruan, Shuoquan; Chen, Bingli; Ran, Jinchuan; Shu, Wen; Chen, Yuelai; Hou, Wenguang (Frontiers in Endocrinology, 2022)
Objective To examine the effect of electroacupuncture on the urodynamics and gut microbiota of rats with stress urinary incontinence (SUI). Materials and methods Thirty 2-month-old female Sprague–Dawley (SD) rats were randomly assigned to 4 groups: normal (N), model (M), nonacupoint electric acupuncture control (NAAC), and electroacupuncture (EA). An SUI rat model was established through vaginal balloon dilatation and bilateral oophorectomy. After various treatments, urodynamic tests were performed, and feces were collected. 16S rRNA sequencing analysis was used to investigate SUI-related changes in the intestinal flora. Results After treatment, compared with those of the M group, the leak point pressure and maximum bladder capacity of the electroacupuncture groups increased (P<0.05). The species community compositions of the N and M groups differed at the genus level, and there were 15 differentially abundant bacterial genera (P<0.05). The Blautia proportion was increased by electroacupuncture treatment (P<0.05) and was significantly positively correlated with the electroacupuncture treatment of SUI (according to Spearman correlation analysis). Conclusion Electroacupuncture treatment can improve signs of urine leakage in rats with SUI rats by increasing the leak point pressure and maximum bladder capacity. The enrichment of Blautia by electroacupuncture treatment enrichment may be related to SUI sign improvement.